Cement-based Repair Materials: A Review of Methods for Assessing Durability - Simandl, Laura; Biparva, Alireza; Gupta, Rishi (Innovations in Corrosion and Materials Science (Discontinued), 2016)
Concrete’s durability is the ability to resist deterioration over time, and maintain its engineered properties like strength, form and aesthetics. Durable concrete is more sustainable and more economical, and a variety of techniques can be used on hardened concrete to evaluate its durability. The techniques outlined are focused on: freeze and thaw and scaling, alkali-silicate reactivity, petrographic examination, abrasion and erosion, chloride content determination, steel reinforcement corrosion potential, RCP, and fluid penetration resistance.
Keywords: sulfate attack